Implementation of contemporary DNA based techniques on traceability process of small ruminant species and products - Laliotis, George P.; Koutsouli, Panagiota; Bizelis, Iosif A. (Journal of Advanced Veterinary and Animal Research, 2018)
Traceability methods in livestock sector through the tracking of animal species, breed or even individuals, has become of utmost importance as a “vehicle” for ensuring consumers’ food safety. The advent of new technology at DNA level has facilitated the convenience and the accuracy of the implementation of traceability methods. The scope of this review is to highlight the most up to date progress on DNA based approaches concerning the traceability procedures for small ruminant species and/or their products, giving emphasis on short tandem repeats (microsatellites) and single nucleotide polymorphisms. The conclusions of this review may be used either from the farmer or the State and other Organisations in order not only to certify traceability throughout the whole food process chain but to ensure also consumers’ food safety. http://doi.org/10.5455/javar.2018.e274